Existential and Architectural Space in the Human World: Gender Aspect - A. V. Yurieva (Дискурс, 2022)
Introduction. Space acts as a basic category for many phenomena of the human world. Therefore, a full understanding and analysis of space is possible only when we take into account the presence of a person in it. The purpose of the study is the need to trace the close interrelation of human existence and space, their mutual influence and interdependence. The relevance of the paper is connected with the need to enlarge the category of space in the gender aspect of being. The research novelty consists in the attempt to systematize the accumulated knowledge in the field of the study of the category of space and its gender characteristics.Methodology and sources. The methodological basis of the work are philosophical analysis and cultural analysis. The main approach in the work is interdisciplinary. We used as sources philosophical works related to the problem of space (M. Heidegger, M. Foucault, M. Merleau- Ponty, G. Marcel) and gender (G. Marcuse, M. Foucault, J. Derrida, J. Lacan, Ju. Kristeva), theoretical works on architecture (A. Ikonnikov, A. Nekrasov, K. Nornberg-Schultz, A. Gabrichevsky), as well as some sociological works (P. Bourdieu, M. Vilkovsky, S.O. Khan- Magomedov). Separate works on semiotics (U. Eco) and the issues of metaphorization in culture (O. Freudenberg, E.S. Kubryakova) provided tangible assistance in the preparation of this text.Results and discussion. Being a fundamental ontological category, space is explored in various aspects of humanitarian discourse. The history of culture shows us the mobility of the categories “masculinity” and “femininity”, therefore, a natural question arises about the regular revision of these concepts, that affect the spatial characteristics of being in a specific historical epoch. In the course of the study, the following results were obtained. Based on the analysis of works from the field of anthropology, the study of the body and gender, as well as by identifying the features of the formation of architectural space, we can say that there is a close relationship between space and person. Our research shows that the body is the background of cognition of the world and the individual oneself, therefore it acts as the basis for the formation of a gender metaphor. We have studied the works of architects, and it was concluded that it is impossible to “catch” a specifically feminine or masculine manner in the professional activity of an architect. The reason is that, first of all, the architect is faced with a specific order and certain technical tasks.Conclusion. As a basic characteristic of human existence, space appears in human existence also as a communicative sphere. The primary bodily experience of space, that a human being gets from birth, largely determines the background of cognition of the world. Moreover, the space can carry gender-marked or gender-neutral information, and that gives us a reason to talk about the problem of perception and influence on a person. This can be traced through the metaphor of the architectural language, the ways of space organizing, highlighting with color, shape and construction. Therefore, architecture is distinguished from other types of art by its great dependence on social reality that generates it, since it is a part of the human living environment.